Reducing health inequalities among girls and adolescent women living in poverty: the success of Bangladesh. (3rd March 2016) - Rousham, Emily K.; Khandakar, Ikhtiar Uddin
Abstract: Background : Bangladesh has made dramatic improvements in the health of girls and women in the last 20 years. This paper examines whether gender inequalities in health are evident among older children and adolescents among extremely poor households and identifies future health challenges for improving the health of girls and women. Subjects and Methods : Gender inequalities in health were examined using data from a school health survey of school children and adolescents ( n  = 900, 6.5–13.5 years). Anthropometric status, household possessions and number of siblings were measured. Under-nutrition was assessed as stunting (height-for-age z -score) and thinness (BMI-for-age z -score). Results : The prevalence of under-nutrition was high (35.3% stunting; 42.4% thinness), but there were no significant differences according to gender or socio-economic indicators (via possession score). Girls had more younger siblings ( p < 0.05), while boys had more older siblings ( p < 0.05). Conclusions : These findings accord with the national picture of successful reductions in gender inequalities in health through low cost, community-based health programmes and education policies targeting the poorest sectors. The prevalence of under-nutrition, however, remains high. Reproductive behaviours may still be influenced by poverty and the gender of existing offspring. Future challenges lie in reducing the adverse health consequences to women and their infants associated with early age at marriage and childbirth.